Metabolic and Structural Signatures of Speech and Language Impairment in Corticobasal Syndrome: A Multimodal PET/MRI Study - Parmera, Jacy Bezerra; Almeida, Isabel Junqueira de; Oliveira, Marcos Castello Barbosa de; Silagi, Marcela Lima; de Godoi Carneiro, Camila; Studart-Neto, Adalberto; Ono, Carla Rachel; Reis Barbosa, Egberto; Nitrini, Ricardo; Buchpiguel, Carlos Alberto; Brucki, Sonia Maria Dozzi; Coutinho, Artur Martins (Frontiers in Neurology, 2021)
Introduction: Corticobasal syndrome (CBS) is a progressive neurological disorder related to multiple underlying pathologies, including four-repeat tauopathies, such as corticobasal degeneration and progressive supranuclear palsy, and Alzheimer's disease (AD). Speech and language are commonly impaired, encompassing a broad spectrum of deficits. We aimed to investigate CBS speech and language impairment patterns in light of a multimodal imaging approach. Materials and Methods: Thirty-one patients with probable CBS were prospectively evaluated concerning their speech–language, cognitive, and motor profiles. They underwent positron emission tomography with [18F]fluorodeoxyglucose (FDG-PET) and [11C]Pittsburgh Compound-B (PIB-PET) on a hybrid PET-MRI machine to assess their amyloid status. PIB-PET images were classified based on visual and semi-quantitative analyses. Quantitative group analyses were performed on FDG-PET data, and atrophy patterns on MRI were investigated using voxel-based morphometry (VBM). Thirty healthy participants were recruited as imaging controls. Results: Aphasia was the second most prominent cognitive impairment, presented in 67.7% of the cases, following apraxia (96.8%). We identified a wide linguistic profile, ranging from nonfluent variant-primary progressive aphasia to lexical–semantic deficits, mostly with impaired verbal fluency. PIB-PET was classified as negative (CBS-A– group) in 18/31 (58%) and positive (CBS-A+ group) in 13/31 (42%) patients. The frequency of dysarthria was significantly higher in the CBS-A– group than in the CBS-A+ group (55.6 vs. 7.7%, p = 0.008). CBS patients with dysarthria had a left-sided hypometabolism at frontal regions, with a major cluster at the left inferior frontal gyrus and premotor cortex. They showed brain atrophy mainly at the opercular frontal gyrus and putamen. There was a positive correlation between [18F]FDG uptake and semantic verbal fluency at the left inferior (p = 0.006, R2 = 0.2326), middle (0.0054, R2 = 0.2376), and superior temporal gyri (p = 0.0066, R2 = 0.2276). Relative to the phonemic verbal fluency, we found a positive correlation at the left frontal opercular gyrus (p = 0.0003, R2 = 0.3685), the inferior (p = 0.0004, R2 = 0.3537), and the middle temporal gyri (p = 0.0001, R2 = 0.3993). Discussion: In the spectrum of language impairment profile, dysarthria might be helpful to distinguish CBS patients not related to AD. Metabolic and structural signatures depicted from this feature provide further insights into the motor speech production network and are also helpful to differentiate CBS variants.